A dopant-free spirobi[cyclopenta[2, 1-b:3, 4-b′]dithiophene] based hole-transport material for efficient perovskite solar cells. Issue 6 (9th September 2015) - Franckevičius, Marius; Mishra, Amaresh; Kreuzer, Franziska; Luo, Jingshan; Zakeeruddin, Shaik Mohammed; Grätzel, Michael
Abstract : A new spiro-cyclopentadithiophene-based hole transport material has been developed for perovskite solar cells exhibiting an excellent power conversion efficiency of 13.4% without the use of any additives and dopants. Abstract : We present the design and synthesis of a promising hole transporting material (HTM) using the 4, 4′-spirobi[cyclopenta[2, 1- b :3, 4- b ′]dithiophene] derivative (spiro-CPDT) as the core and triarylamines as terminal units. The implementation of the new HTM in CH3 NH3 PbI3 -based perovskite solar cells exhibited an excellent overall power conversion efficiency (PCE) of 13.4% without the use of any dopants and additives which is comparable to 15.0% obtained using p-doped spiro-MeOTAD-based devices. Furthermore, the device based on the new HTM generated a slightly higher open circuit voltage ( V OC ) of 971 mV compared to a spiro-MeOTAD ( V OC = 951 mV) based device. The present results demonstrate that spiro-CPDT could be an excellent building block to prepare dopant-free HTMs for perovskite solar cells and holds promise to replace the p-doped spiro-OMeTAD, which is important for the fabrication of cost-effective devices in the future.